2020
DOI: 10.1136/esmoopen-2020-001034
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific aspects of epidemiology, molecular genetics and outcome: primary brain tumours

Abstract: Recent years have seen a great interest in sex-specific aspects of many diseases, including cancer, in part because of the assumption that females have often not been adequately represented in early drug development and determination of safety, tolerability and efficacy in clinical trials. Brain tumours represent a highly heterogeneous group of neoplastic diseases with strong variation of incidence by age, but partly also by sex. Most gliomas are more common in men whereas meningiomas, the most common primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 49 publications
0
17
1
Order By: Relevance
“…The present data did not show significant sex differences in the disease burden of CNS cancer, but this needs to be confirmed, because the incidence rate, for example, varies between men and women when referring to literature from different data sources 26–28. As reported, men had higher incidences of germ cell tumours, haematopoietic neoplasms and glioblastoma, while women had higher incidences among other neuroepithelial tumours and malignant meningioma 29 30. Thus, the current study with all histological subtypes combined could not detect the potential differences between men and women.…”
Section: Discussioncontrasting
confidence: 57%
“…The present data did not show significant sex differences in the disease burden of CNS cancer, but this needs to be confirmed, because the incidence rate, for example, varies between men and women when referring to literature from different data sources 26–28. As reported, men had higher incidences of germ cell tumours, haematopoietic neoplasms and glioblastoma, while women had higher incidences among other neuroepithelial tumours and malignant meningioma 29 30. Thus, the current study with all histological subtypes combined could not detect the potential differences between men and women.…”
Section: Discussioncontrasting
confidence: 57%
“…Previous studies have indicated that the incidence rates of glioma tended to be associated with age and gender. 25 Age stratified analysis showed rs13177623 had a lower risk of glioma at age ≥ 40 years, while rs11168100, rs12654195 and rs17796757 were associated with the susceptibility to glioma at age < 40 years. These indicate that the contribution of CARMN polymorphisms to glioma risk was associated with age exposures.…”
Section: Discussionmentioning
confidence: 90%
“…Epidemiologically, neuroepithelial tumors, including all grades of gliomas, are more frequently observed in men. 24,25 In terms of survival, male patients with glioblastoma 24,[26][27][28] and grade 3 gliomas 29 present with shorter survival than female patients. Therefore, although still controversial, 28,30 male patients with malignant gliomas had worse survival.…”
Section: Discussionmentioning
confidence: 99%